Democracy in Times of Crises
XII, 231 p. 4 illus.
Keywords: Inspired by the democratic origins of the Greek naval victory at Salamis, the book discusses the current pressing issues of democracy worldwide. In 12 carefully selected chapters, well-renowned scholars from around the globe discuss topics such as Brexit, Euroscepticism, or the rise of populism. The authors further analyze various aspects of democracy, as well as various types of democratic regimes, such as mixed government, direct democracy, and cases of quasi democracies. While doing so, they relate this discussion to the pivotal question of how the quality of democracy today can be improved, seeking answers and solutions to current pending problems at the global level. This book is the second out of two edited volumes as a sequel of an international academic conference titled Salamis and Democracy: 2500 Years After that took place between October 3rd and October 5th, 2020, on the occasion of the 2500th anniversary of the great historical event of the Battle of Salamis, which saved Greek culture and the newly founded democratic regimes throughout the Hellenic world during the Classical period (508-323 BCE). The book is a must-read for scholars and students of political science, economics, and law, as well as policy-makers interested in a better understanding of democracy, governance, populism, social choice, and constitutional law.